2008
DOI: 10.1038/nrd2764
|View full text |Cite
|
Sign up to set email alerts
|

Lacosamide

Abstract: In August 2008, lacosamide (Vimpat; UCB), was granted market authorization by the European Commission as an adjunctive therapy for partial-onset seizures with or without secondary generalization in patients with epilepsy. It was approved by the FDA as an adjunctive therapy for partial-onset seizures in October 2008.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 13 publications
0
85
0
Order By: Relevance
“…The novel antiepileptic drug lacosamide ((R)-N-benzyl 2-acetamido-3-methoxypropionamide) (LCM, 4 Vimpat) (1) has been recently approved in the U.S. and Europe for adjunctive treatment of partial-onset seizures in adults (2)(3)(4) and can be effective in cases of refractory epilepsy (5). Experimental data suggest two modes of action.…”
Section: The Anti-epileptic Drug (R)-lacosamide ((2r)-2-(acetylamino)mentioning
confidence: 99%
“…The novel antiepileptic drug lacosamide ((R)-N-benzyl 2-acetamido-3-methoxypropionamide) (LCM, 4 Vimpat) (1) has been recently approved in the U.S. and Europe for adjunctive treatment of partial-onset seizures in adults (2)(3)(4) and can be effective in cases of refractory epilepsy (5). Experimental data suggest two modes of action.…”
Section: The Anti-epileptic Drug (R)-lacosamide ((2r)-2-(acetylamino)mentioning
confidence: 99%
“…13 One of these compounds, (R)-N-benzyl 2-acetamido-3-methoxypropionamide 6 (lacosamide, (R)-2), is a first-in-class AED marketed in 34 countries, including the United States. 14 Studies have shown that (R)-2 preferentially transitioned voltage-gated Na + channels (VGSCs) to the slow inactivation state without affecting fast inactivation. 15−17 Na + channel slow inactivation promotion is a powerful mechanism to control the hyperexcitable neuron in the epileptic patient, where neurons are either rapidly firing or in a sustained, depolarized state.…”
Section: Introductionmentioning
confidence: 99%
“…Lacosamide is a novel functionalized amino acid that enhances inactivation of voltagegated sodium channels (Curia et al, 2009;Perucca et al, 2008b). Lacosamide was approved in Europe in 2008 for partial-onset seizures in patients 16 years and older (Chung et al, 2010).…”
Section: Lacosamidementioning
confidence: 99%